The Effect of Differentiated Instruction on Vocational High School Students’ Mathematical Understanding in Terms of Visual, Auditory, and Kinesthetic Learning Styles - Ilham Wahyudi; Nailul Authary; Nazariah Nazariah; Risy Mawardaty (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2025)
This study aims to determine the effect of differentiated learning on mathematical understanding among vocational high school (SMK) students, considering their visual, auditory, and kinesthetic learning styles. The research method employed was a quasi-experiment with a pre-test and post-test control group design. The sample consisted of 46 students divided equally into an experimental group (differentiated learning) and a control group (conventional learning). Data collection instruments included learning style questionnaires and mathematical understanding tests on the System of Linear Equations with Two Variables (SPLDV). Data analysis was performed using SPSS 27, including normality tests, paired sample t-tests, homogeneity tests, independent sample t-tests, and N-gain score calculations. The results indicated that: (1) students possess varied learning styles, predominantly auditory and kinesthetic; (2) there was a significant difference (Sig. 0.05) in pre-test and post-test scores, with the experimental class mean increasing from 53.30 to 89.43, while the control class increased from 51.43 to 75.39; and (3) differentiated learning showed a high effectiveness category with an N-gain of 77%, compared to the conventional method's 46.2% (less effective). These findings confirm that differentiated learning significantly enhances mathematical understanding.